ANALISIS PENGENDALIAN KUALITAS PRODUKSI DEPARTEMEN HIGHSPEED PADA PT VOLEX INDONESIA - Simanjuntak, Debora; Aji Prasetyo, Bahariandi (LPPM Universitas Putera Batam, 2025)
Product quality is a crucial factor in maintaining a company's competitiveness in the market. Therefore, production quality control is crucial to ensure each product meets established standards. This study aims to analyze the factors causing product defects and implement solutions to improve quality and reduce rework. The quantitative method used is the Six Sigma approach with the DMAIC (Define, Measure, Analyze, Improve, Control) stages. The results show that the dominant types of defects include pad lifted, solder wire lifted, and solder bending, which contribute significantly to product rejection and rework. Based on Nvidia's 2024 production data with a total output of 900,000 units and a total of 85,487 defects, the DPMO value was obtained at around 333,300, indicating a sigma level in the range of 3, far from the Six Sigma target (3.4 DPMO). Analysis using a fishbone diagram identified the causes of defects originating from human, machine, material, method, measurement, and environmental factors. Problems included a lack of discipline, suboptimal machine conditions, inappropriate raw materials, the absence of written SOPs, and an unsupportive work environment. The implications of these findings form the basis for continuous improvement in the company's quality control system.